(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: In the municipalities of Sannazzaro de’ Burgondi and Ferrer Erbognone (District of Lomellina, Pavia, Lombardy, Italy), an oil refinery is operating since 1963. In 2008, the company running the plant (eni S.p.A.) asked the competent bodies the permission for building a new facility (“EST”). The present work is aimed at evaluating the ante-operam health impacts of the existing facility refinery. Methods: A case-control study design was implemented. Cases were subjects admitted to hospital in 2002-2014 due to acute respiratory, cardiovascular or gastrointestinal conditions. Controls were selected among those who had not been hospitalised in that timespan. Cases and controls had to be alive at enrolment, aged 20-64 years, and were frequency-matched by age, gender and municipality. Data were extracted from the health insurance registry and from Hospital Discharge Records (ATS Pavia). Enrolled subjects were asked to complete a mailed survey. Environmental exposure was the fallout of refinery emissions (PM10) at participants’ homes, as predicted by an AERMOD model. Results: 541 respondents (125 cases, 416 controls) were included in the analyses. Response bias was excluded. Individual PM10 exposure was not significantly different between cases and controls, while it was significantly associated with municipality (being higher in Sannazzaro). The crude effect estimate of PM10 over case/control status indicated a not-significant excess of hospitalisation with the increase in PM10 exposure. Multivariate analyses confirmed those results. Conclusion: Findings indicate a possible excess of hospitalisation risk in most exposed people, but the effect is not statistically significant and may be affected by bias.